A new method of colorimetric assay of beta-lactamase suitable for estimation of beta-lactamase inhibition in crude microbial culture filtrates - Basu, M; Sanyal, A K; Banerjee, A B (Folia microbiologica, 2002)
A simple procedure is described for the rapid assay of beta-lactamases suitable for use in the quantitation of beta-lactamase inhibition in crude culture filtrates of soil microbes. The proposed method is based on measuring the blue reaction product (lambda max 750 nm) formed during reduction of phosphomolybdic acid with reducing products generated from beta-lactam hydrolysis and is not influenced significantly by the metabolites of microbial culture filtrates which often interfere with conventional beta-lactamase assay techniques.
Keywords: Fungi; Culture Media; kyseliny fosforečné; kultivační média; beta-Lactamases; Microbial Sensitivity Tests; beta-Lactamase Inhibitors; houby; Soil Microbiology; inhibitory beta-laktamasy; beta-laktamasy; Enzyme Inhibitors; Molybdenum; hydrolýza; oxidace-redukce; beta-laktamy; Actinobacteria; beta-Lactams; mikrobiální testy citlivosti; molybden; kolorimetrie; půdní mikrobiologie; Oxidation-Reduction; Phosphoric Acids; inhibitory enzymů; Hydrolysis; Colorimetry